Local Wisdom Based on Traditional Cultural Values ​​of the Batak's Karo Community - Bancin, M. Rizky Alqodry; Ananda, Faisar; Iwan, Iwan (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2025)
This research aims to describe local wisdom based on the traditional cultural values ​​of the Batak Karo community, especially in the traditional inheritance law system. This research uses a qualitative approach with a case study method. Data was obtained from various sources, including literature, interviews with traditional leaders, and direct observations of inheritance law practices in Karo Batak society. Data collection techniques include in-depth interviews, document study, and participant observation. Data analysis was done through data reduction, presentation, and inductive conclusion drawing. The research results show that Karo Batak's customary inheritance law is based on a patrilineal system, where the eldest son is the main heir. However, in certain situations, women also have the right to inheritance, especially if no sons are in the family. Inherited assets, especially land or hereditary assets, tend to be inherited patrilineally to maintain the continuity of the bloodline. In addition, the role of ancestors is very influential in the inheritance distribution process, with strong traditional mechanisms for resolving conflicts. The conclusion of this research shows that although Karo Batak's traditional inheritance law is still practiced, modernization has brought challenges and adaptations to this system. Urbanization, education, and the influence of national laws cause some families to adopt a combination of customary law and state law to suit social and economic needs. Therefore, it is recommended that there be a policy that accommodates cultural values ​​and aspects of justice in inheritance practices in Karo Batak society so that it remains relevant to current developments.